Study and modeling of melt pool evolution in selective laser melting process of SS316L - Tan, J. L. (2019)
In this paper, the melting of stainless steel 316L using Computational Fluid Dynamics to observe the melt pool characteristics is studied. The simulation model allows the observation of the molten pool flow during the selective laser melting process due to Marangoni’s effect and recoil pressure. Furthermore, different parameters are tested to show their effects on the melt pool and track formation. Different laser powers, as well as scanning speeds, were used to study the effects they have on the melt pool characteristics. The results were used to determine the relationships between these factors and the melt pool characteristics.